CALCULATION OF GAMMA FUNCTIONS SIGNIFICANCES - Denysiuk, V.P.; Rybachuk, L.V. (Proceedings of National Aviation University (archive), 2005)
The existing variants of the Euler’s gamma function presentation are investigated in view of their application for calculations of this function values. The accuracy of calculations has been investigated experimentally depending on these variants parameters.